ヤカン ノ デンリソウ キュウシュウ 1 ダイ2 8ジ ナンキョク カンソクセン ジョウ タンパ デンカイ キョウド ソクテイ - 若井, 登; ワカイ, ノボル; 大瀬, 正美; オオセ, マサミ; 田之畑, 一男; タノハタ, カズオ; WAKAI, Noboru; OSE, Masami; TANOHATA, Kazuo (国立極地研究所, 1971)
P(論文) Observations of the nighttime ionospheric absorption have been carried out since 1958 on board the ship for the Japanese antarctic research. Field intensities of the HF standard frequency signals at different frequencies were measured during hours around midnight. In this paper, techniques of the measurement for extracting a relatively small quantity of the nighttime absorption are described. Existence of the absorption is confirmed from the fact that the rate of decrease of field intensities against the ground range at a lower frequency is much larger than that at a higher frequency. Moreover, the dependence of absorption upon the solar activity is found out from the measurement over nine years in the declining epoch of the last solar cycle. A provisional expression for estimating the nighttime absorption is proposed. departmental bulletin paper